THE INFLUENCE OF CHARACTER EDUCATION ON ELEMENTARY SCHOOL STUDENTS’ SOCIAL BEHAVIOR - Muhammad Sabir; Harianta Sembiring; Rudy Surbakti; Ahmad Yani; Risa Juliadilla (International Journal of Educatio Elementaria and Psychologia, 2025)
Social behavior plays a crucial role in shaping students’ interpersonal relationships and their ability to function effectively in a community. However, the increasing prevalence of negative behaviors such as bullying and lack of empathy among elementary school students has highlighted the need for effective interventions. Character education, which focuses on fostering ethical values and social skills, has emerged as a promising approach to address these challenges. This study investigates the influence of character education programs on the social behavior of elementary school students. A quasi-experimental design was employed, involving 100 students divided into an experimental group that received character education lessons and a control group that followed the standard curriculum. Data were collected using behavioral observation checklists, teacher evaluations, and student self-assessment questionnaires. The findings revealed a significant improvement in the social behavior of students in the experimental group, including increased empathy, cooperation, and conflict resolution skills. Teachers noted enhanced classroom interactions and reduced instances of negative behaviors.